2015
DOI: 10.1016/j.jcv.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus load at treatment initiation is predictive of time to resolution of viremia and duration of therapy in hematopoietic cell transplant recipients

Abstract: Background Preemptive antiviral therapy relies on viral load measurements and is the mainstay of cytomegalovirus (CMV) prevention in hematopoietic cell transplant (HCT) recipients. However, optimal CMV levels for the initiation of preemptive therapy have not been defined. Objectives To evaluate the relationship between plasma CMV DNA levels at initiation of preemptive therapy with time to resolution of viremia and duration of treatment. Study Design Retrospective analysis of HCT recipients undergoing seria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 23 publications
3
25
0
Order By: Relevance
“…It should be highlighted that both this approach and ours spare the need for PET administration in a notable percentage of patients who are capable of controlling CMV replication by themselves, thus potentially reducing the toxicity inherent in the use of nucleoside analog anti‐CMV drugs. Other studies, in contrast, advocate initiating PET at very low CMV DNA loads (<150 IU/mL) aimed at reducing the length of antiviral treatment needed to clear CMV DNAemia . Unfortunately, a direct comparison between these studies and ours is not straightforward because of a number of factors, including the use of different PCR assays and criteria for initiation of PET and patients’ baseline and post‐transplant characteristics in each cohort.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…It should be highlighted that both this approach and ours spare the need for PET administration in a notable percentage of patients who are capable of controlling CMV replication by themselves, thus potentially reducing the toxicity inherent in the use of nucleoside analog anti‐CMV drugs. Other studies, in contrast, advocate initiating PET at very low CMV DNA loads (<150 IU/mL) aimed at reducing the length of antiviral treatment needed to clear CMV DNAemia . Unfortunately, a direct comparison between these studies and ours is not straightforward because of a number of factors, including the use of different PCR assays and criteria for initiation of PET and patients’ baseline and post‐transplant characteristics in each cohort.…”
Section: Discussionmentioning
confidence: 93%
“…9 These data suggest that PET should be started as soon as possible to keep CMV DNA loads to a minimum. Two recent reports support the suitability of this approach 3,8 ; Tan and colleagues 3 showed that initiation of PET at low CMV DNA loads results in shorter episodes of CMV DNAemia and courses of antiviral therapy. In turn, Camargo et al 8 concluded that CMV DNA peak levels ≥ 150 IU/mL associate with a drastically reduced probability of spontaneous CMV DNAemia clearance.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…These data are difficult to reconcile with earlier findings demonstrating that prophylactic administration of ganciclovir at engraftment and delaying the start of ganciclovir until high-grade antigenemia resulted in similar survival rates [11], and thus must be confirmed in multicenter prospective studies. Likewise, the idea that early initiation of pre-emptive therapy (at viral loads as low as 135 IU/ml) may result in shorter courses of antiviral therapy [12] merits further research. Until then, to limit drug overexposure and thus toxicity, the focus must be placed on treating as few patients as possible, without compromising their safety, and using antiviral treatment courses as short as possible, without increasing the patient's risk of relapsing/recurrent episodes and late end-organ disease.…”
mentioning
confidence: 99%